An Understanding of the Auditor's Professional Ethics and its Importance in the Auditor's Work (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The principles of professional ethics, on the one hand, emphasize the auditor's responsibility to society, and on the other hand, organizing his activities based on these principles protects the auditor from the unpleasantness of the work process and subsequent work.